Respuesta :
Answer:
-10
Step-by-step explanation:
Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Remember to follow PEMDAS.
First, distribute 2 to all terms within the parenthesis:
2(x + 3) = 2(x) + 2(3) = 2x + 6
2x + 6 = x - 4
Isolate the variable, x. Subtract 6 and x from both sides
2x (-x) + 6 (-6) = x (-x) - 4 (-6)
2x - x = -4 - 6
x = -10
-10 is your answer for x.
~
Answer:
x=-10
Step-by-step explanation:
2(x + 3) = x - 4
Distribute the 2
2x+6 = x-4
Subtract x from each side
2x-x+6 = x-x-4
x+6 = -4
Subtract 6 from each side
x+6-6 = -4-6
x=-10